2021
DOI: 10.1111/ffe.13530
|View full text |Cite
|
Sign up to set email alerts
|

On the variability in static and cyclic mechanical properties of extruded 7075‐T6 aluminum alloy

Abstract: The present paper investigates the variability in the static and cyclic properties of two nominally identical supplies of the aeronautical Al grade 7075-T6. Samples were extracted from extruded bars of 15 and 60 mm diameter and with slightly different chemical composition. Noticeable differences were found in tensile strength, total elongation, and low-and high-cycle fatigue strength, despite the nearly identical hardness value. The diverse mechanical behavior has been imputed to different extrusion ratio and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 28 publications
0
1
0
Order By: Relevance
“…According to the given data in reference [31], the final fracture stress is about 663 MPa, percentage of the cross-section reduction is 15%, and the Poisson's ratio will be 0.33.…”
Section: Experiments and Samplesmentioning
confidence: 99%
“…According to the given data in reference [31], the final fracture stress is about 663 MPa, percentage of the cross-section reduction is 15%, and the Poisson's ratio will be 0.33.…”
Section: Experiments and Samplesmentioning
confidence: 99%
“…Figure 5 presents the yield surface translation based on the A-V hardening rule for different testing materials with DIFs of 0, 1%, and 2%. This figure includes stress-strain curves developed by the Ramberg-Osgood equation [30], at which materials constants for Al7075-T6 are taken from [34]. The yield translation in Figure 5c is presented for the plane stress condition and in a two-dimensional coordinate σ 1 − σ 2 system.…”
Section: Yield Surface Evolutionmentioning
confidence: 99%
“…Wei [16] studied the anisotropy of the mechanical properties of 7050 alloy sheets in different directions, and its anisotropy is mainly affected by recrystallisation. Benedetti et al [17] found that there were noticeable differences in tensile strength, total elongation and low- and high-cycle fatigue strength for 7075-T6 extruded bars with nearly identical hardness. He also proposed an equation relating the yield stress and the size of the maximum intermetallic precipitate to predict the fatigue endurance.…”
Section: Introductionmentioning
confidence: 99%